Liability and culpability - Oliver, M (2018)
A person’s choices and actions can make them liable to defensive harms. Yet the nature of moral liability, its limits and justifications, are the subject of considerable debate. This thesis is a contribution to those debates. Its starting point is the idea that we can better understand both liability and culpability by examining the connection between the two. I offer an account of moral liability according to which a liability is a reason to give less weight to the interests of the liable person. To defend this account I discuss proportionality, necessity, and hard cases of aggregation and multiple justifications. I justify liabilities by appealing to the significance of our choices, the costs attached to those choices, and the reasons we have for making them. Culpable choices, such as the decision to attack another, can make a person liable to defensive harms. Our enforceable duties are closely related to liabilities, yet do not themselves directly explain or justify our liabilities. I discuss the relationship between moral responsibility, causal responsibility, and liability. I argue that causal responsibility for a threat of harm is not a necessary condition of liability to be harmed in the prevention of that threat. My account of the justification for liability is directly linked to my account of the nature of culpability. I argue that a person is culpable to the extent that they manifest insufficient sensitivity to action-guiding moral reasons in the exercise of their agency. I elaborate this account to show how it fits in between volitionist and attributivist theories of culpability. I discuss the ways in which we can be culpable for past actions and for our possible future actions, the problem of moral luck, of moral ignorance, the relationship between culpability and permissibility, and excuses that do not deny culpability.